Recovery of the cortical chloroplast layer in the green alga Chara after local irradiation - Hoepflinger, Marion C.; Höftberger, Margit; Sommer, Aniela; Hohenberger, Florian; Schagerl, Michael; Foissner, Ilse (Frontiers in Plant Science, 2025)
The cytoplasm of characean internodal cells is characterized by a stationary layer of cortical chloroplast files and a mobile endoplasm moving along subcortical actin bundles. Occasionally, chloroplasts detach from the cortex and are passively carried along with the endoplasmic flow. Previous studies revealed that local irradiation with intense light causes chloroplast bleaching followed by a release into the endoplasm (“window formation”). We found that endoplasmic chloroplasts of Chara australis resettle at the window and align parallel to the streaming direction. The process takes several weeks with neither chloroplast division nor growth of proplastids being involved. Both release and re-attachment are actin-dependent. Resettled chloroplasts showed slightly, but significantly lower maximum quantum efficiency (Fv/Fm) values as compared with control regions. Extremely low Fv/Fm values were measured in chloroplasts at the border of the window even after three months indicating longevity, although with serious damage. In higher plants, a protein complex is responsible for the motility and anchorage of chloroplasts, with CHUP1 (CHLOROPLAST UNUSUAL POSITIONING 1) being an essential part. We discovered a homologous form CaCHUP1, encoding a polypeptide of 1201 amino acids with a calculated molecular mass of about 130 kDa. When transiently expressed in epidermal cells of Nicotiana benthamiana leaves, fluorescently tagged CaCHUP1 localizes to chloroplasts. We assume that CaCHUP1 is involved in the anchorage of chloroplasts and in the polymerization of actin filaments, but not in active movement. Our study revealed that endoplasmic chloroplasts can re-anchor at the cell cortex thereby refilling chloroplast-free regions, which we interpret as a repair mechanism after various kinds of damage. It confirms that chloroplasts use different strategies for repositioning, either via polymerization of cp-actin or via cytoplasmic streaming.